Implementation of Entrepreneurship Course in Maritime Higher Education - Vidya Selasdini (Yayasan Keluarga Guru Mandiri, 2024)
Entrepreneurship course is one of the subjects given to seventh semester cadets majoring in Sea Transportation and Port Management at the College of Shipping. This study aims to determine the implementation as well as an evaluation for further entrepreneurship learning. The evaluation was conducted using the Kirkpatrick evaluation model developed by Mullins which consists of four aspects: satisfaction, learning, behaviour and impact. The method used is a combination of quantitative and qualitative with data analysis in the form of percentages. The sample was taken from 140 cadets who had completed the entrepreneurship course. Data was collected through a questionnaire administered via google form. The results showed that the level 1 evaluation of cadets' satisfaction in learning showed an average score of 71% satisfied learning entrepreneurship and 29% dissatisfied. From the level 2 evaluation, it was obtained that the average cognitive, affective and psychomotor learning outcomes had increased. Level 3 evaluation of entrepreneurial behaviour obtained an average increase of 20 points. Level 4 evaluation of the impact of learning obtained 82% of cadets think it is suitable to be continued, and 75% think entrepreneurship learning is effective in making cadets become entrepreneurs, and 72% form cadets to carry out business activities.